Procurement of Equipment to Support Vegetable Ice Cream Production for Residents of Duwet Village, Kec. Tumpang Kab. Malang - Eny Widiyowati; Baroroh Lestari; Evi Suwarni; Putri Sekarsari; Alvin Nouval; Prima Beauty Kartikasari (Transpublika Publisher, 2024)
This community service (PKM) program aims to improve the production field which is identified as having weaknesses in the vegetable ice cream producing community of Duwet Village, Tumpang District, Malang Regency. The partner's problem that can be identified from the production sector is the production support equipment that is still not fully available. The priority solution provided was training on hygienic production processes using the donated equipment in the form of a frezeer and blender. The results of this activity are proven to improve the quality and quantity of vegetable-based ice cream produced by residents. Suggestions from this service activity are 1) increase the number of production equipment in line with the increasing demand for vegetable ice cream. 2) It is necessary to develop innovative ice cream products with other vegetable- based ingredients such as carrots, spinach, or pumpkin which also have high nutritional value. 3) It is necessary to develop branding and marketing strategies to introduce vegetable ice cream to a wider market. 4) Counseling on more efficient production techniques, business management, and product development should be conducted regularly. 5) In order to maintain product quality consistency, it is recommended that program beneficiaries implement a quality management system. 6) It is necessary to establish a Joint Business Group (KUB) that is responsible for the production, management, and marketing of vegetable ice cream.